2010
DOI: 10.1186/1746-4811-6-26
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of barley stripe mosaic virus as a gene silencing vector in barley roots and in Brachypodium distachyon and oat

Abstract: BackgroundGene silencing vectors based on Barley stripe mosaic virus (BSMV) are used extensively in cereals to study gene function, but nearly all studies have been limited to genes expressed in leaves of barley and wheat. However since many important aspects of plant biology are based on root-expressed genes we wanted to explore the potential of BSMV for silencing genes in root tissues. Furthermore, the newly completed genome sequence of the emerging cereal model species Brachypodium distachyon as well as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
61
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 58 publications
(92 reference statements)
2
61
0
Order By: Relevance
“…Both approaches have been used with Brachypodium (Olsen et al, 2006;Demircan and Akkaya, 2009;Pacak et al, 2010), and recently, a T-DNA mutation in Brachypodium has been complemented with an Arabidopsis ortholog, bridging dicotyledonous and monocotyledonous models (Vain et al, 2011). In addition, biotechnological approaches for crop improvement can be tested by introducing and expressing heterologous genes (e.g.…”
Section: Transformation and T-dna Mutantsmentioning
confidence: 99%
“…Both approaches have been used with Brachypodium (Olsen et al, 2006;Demircan and Akkaya, 2009;Pacak et al, 2010), and recently, a T-DNA mutation in Brachypodium has been complemented with an Arabidopsis ortholog, bridging dicotyledonous and monocotyledonous models (Vain et al, 2011). In addition, biotechnological approaches for crop improvement can be tested by introducing and expressing heterologous genes (e.g.…”
Section: Transformation and T-dna Mutantsmentioning
confidence: 99%
“…Very recently, Cucumber mosaic virus-based VIGS in maize is reported (Wang et al, 2016) BMV and BMV-based vectors are frequently used for VIGS in some monocot plants. However, both virus vectors do not work in many other monocot species and not all cultivars within a particular host species (Ding et al, 2006;Pacak et al, 2010).…”
mentioning
confidence: 99%
“…By contrast, to date only four RNA viruses and one DNA virus have been modified as vectors for VIGS in monocot species, of which, Barley stripe mosaic virus (BSMV)-based VIGS has been applied for functional genomics in barley (Hordeum vulgare L.) and wheat (Triticum aestivum; Holzberg et al, 2002;Tai et al, 2005;Meng et al, 2009;Pacak et al, 2010;Yuan et al, 2011); Brome mosaic virus (BMV) in rice (Oryza sativa L.), barley, and maize (Zea mays L.; Ding et al, 2006); Bamboo mosaic virus and its satellite RNA in N. benthamiana and Brachypodium distachyon (Liou et al, 2014); and Rice tungro bacilliform virus in rice (Purkayastha et al, 2010). Very recently, Cucumber mosaic virus-based VIGS in maize is reported (Wang et al, 2016) BMV and BMV-based vectors are frequently used for VIGS in some monocot plants.…”
mentioning
confidence: 99%
“…Notably, we found complete silencing of pSL038-1/G two weeks after inoculation in barley plants. A similar study has shown that BSMV-VIGS can be used for down regulation of important genes in B. distachyon (Pacak et al, 2010). VIGS is a fast and reliable method for stable knock-down of a desired gene which would produce a phenotype; therefore it could be employed as a quick method for cereal species where stable genetic transformation is required but a very laborious choice (Wege et al, 2007;Ma et al, 2012).…”
Section: Effect Of Silencing On Plant Growth and Physiologymentioning
confidence: 99%